Analisis Pengaruh Produksi Perikanan, Ekspor Perikanan dan Angka Konsumsi Ikan Terhadap Pertumbuhan Ekonomi Sektor Perikanan di Indonesia - Marjusni, Indri; Idris, Idris (Universitas Negeri Padang, 2023)
This study aims to determine and analyze the effect of Fishery Production, Fishery Exports and Fish Consumption figures on the Economic Growth of the Fisheries Sector in Indonesia. This study uses panel data from 2015 to 2020 in 33 provinces in Indonesia, sourced from the Ministry of Maritime Affairs and Fisheries of the Republic of Indonesia. Before using the regression, the Chow test and Hausman test were carried out and the estimation results showed that the selected model was the Fixed Effect Model (FEM). The results showed that: (1) Fishery production has a negative and significant effect on the economic growth of the fisheries sector in Indonesia (2) Fishery exports have a positive and significant effect on the economic growth of the fisheries sector in Indonesia (3) Fish consumption figures have a positive and significant effect on the economic growth of the fisheries sector in Indonesia. Based on the research results, it is suggested that for further research it is necessary to examine other independent factors and variables that influence the economic growth of the fisheries sector.